Сomparative analysis of two-channel angular discriminators under linear scanning of the antenna radiation pattern - M. M. Bulash; S. V. Shaliapin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The comparative analysis results of various types of discriminators operating under linear scanning of the radiation pattern, as well as the single-pulse direction finding discriminator using the comparison amplitude method are presented.